2020
DOI: 10.1001/jamanetworkopen.2020.22713
|View full text |Cite
|
Sign up to set email alerts
|

Hard Truths About Suicide Prevention

Abstract: Suicide accounts for nearly 50 000 deaths annually in the US, making it the second leading cause of death among persons 10 to 34 years of age. 1 Although psychiatric illness is associated with elevated rates of death from a range of causes, from cardiovascular disease to cancer, 2 suicide stands out: it occurs precipitously, disproportionately involves younger individuals, and is generally viewed as more preventable. Suicide represents a particular challenge in the military because soldiers are placed in extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…The positive predictive value across all our models was quite low (e.g., 0.04-0.05). This is consistent with a recent systematic review by Belsher et al (2019) focused on predictive models, findings from screening studies, and is reflective the key challenge in suicide risk screening-suicide is a low base rate problem (Perlis & Fihn, 2020). Predictive accuracy can vary by the rarity of the behavior selected for the outcome, with lower PPVs observed for deaths, but higher PPVs possible with relatively more outcomes such as suicide-related ED visits or suicide attempts.…”
Section: Main Findingssupporting
confidence: 87%
“…The positive predictive value across all our models was quite low (e.g., 0.04-0.05). This is consistent with a recent systematic review by Belsher et al (2019) focused on predictive models, findings from screening studies, and is reflective the key challenge in suicide risk screening-suicide is a low base rate problem (Perlis & Fihn, 2020). Predictive accuracy can vary by the rarity of the behavior selected for the outcome, with lower PPVs observed for deaths, but higher PPVs possible with relatively more outcomes such as suicide-related ED visits or suicide attempts.…”
Section: Main Findingssupporting
confidence: 87%
“…This is consistent with a recent systematic review by Belsher et al 23 focused on predictive models, findings from screening studies, and is reflective of the key challenge in suicide risk screening – suicide is a low base rate problem. 45 Our false positive rates were considerably lower than those found in previous studies, 46 but still represent potential inappropriate use of resources and/or a potential source of distrust or source of fatigue in procedures. 47 While our work and the work of others show suicide risk models can accurately identify risk, depending on how they are operationalized, these models can generate additional workload for clinicians by necessitating response to false positives and strategies for responding to alerts on patients.…”
Section: Discussioncontrasting
confidence: 61%
“…Such a focus may be critical given the challenges in developing reliable risk stratification and effective suicide prevention strategies. 10 Indeed, a study 11 of 135 US Army soldiers who died of suicide found that firearm ownership and modifiable aspects of ownership, such as gun storage, were associated with risk. 11 To better understand the characteristics of individuals with depression who own or plan to purchase firearms, we used data from 2 waves of a large national survey conducted between April and July 2021.…”
Section: Introductionmentioning
confidence: 99%